2016
DOI: 10.1590/0102-311x00048515
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência da assistência domiciliar prestada à população idosa brasileira e fatores associados

Abstract: Avaliar a prevalência e os fatores associados à assistência domiciliar na população idosa brasileira. Estudo transversal de base populacional com indivíduos de 60 anos ou mais, residentes na área urbana de 100 municípios, localizados em 23 estados brasileiros. Foi utilizado modelo de regressão de Poisson para análise bruta e ajustada. Foram entrevistados 6.624 idosos e a prevalência da assistência domiciliar foi de 11,7%. Após ajuste, a ocorrência foi maior entre as mulheres, nos mais velhos, com menor escolar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0
27

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 23 publications
2
11
0
27
Order By: Relevance
“…20 A study conducted in the city of São Paulo found that the presence of hypertension increases by 39% the chance of elderly people becoming dependent for the BADLs and that heart disease, arthropathy, and lung disease increase by 82%, 59%, and 50%, respectively, the chances of these individuals developing dependence. 19 Diabetes mellitus alone did not have a statistically significant relationship with dependence for the activities of daily livin, 14 corroborating with the data described in Table 2.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…20 A study conducted in the city of São Paulo found that the presence of hypertension increases by 39% the chance of elderly people becoming dependent for the BADLs and that heart disease, arthropathy, and lung disease increase by 82%, 59%, and 50%, respectively, the chances of these individuals developing dependence. 19 Diabetes mellitus alone did not have a statistically significant relationship with dependence for the activities of daily livin, 14 corroborating with the data described in Table 2.…”
Section: Discussionsupporting
confidence: 80%
“…Social, economic and demographic aspects such as income, schooling, gender, age and marital status and the presence of chronic diseases such as SAH and DM have been identified as compromising factors for the functional capacity in this population. 14 Regarding the presence of comorbidities, 57% of the respondents report suffering from SAH and 23% of them have concomitant SAH and DM, which is common in this age group. This reality was also found in a study conducted with 150 elderly individuals in a municipality in the inland of Bahia, where it was found that a percentage of 21.5% of the participants suffer from DM and 40.8%, from SAH.…”
Section: Discussionmentioning
confidence: 98%
“… Palavras-chave: assistência domiciliar; cuidadores; necessidades e demandas de serviços de saúde; custos de cuidados de saúde. DOI: http://dx.doi.org/10.1590/S0103-73312019290214 Physis: Revista de Saúde Coletiva, Rio de Janeiro, v. 29(2), e290214, 2019 | Página 2 de 23 Introdução O envelhecimento e a cronificação de doenças nas populações têm levado os governos a repensarem o modelo de atenção em saúde, provendo políticas públicas específicas, o financiamento de estruturas de apoio, a avaliação e o monitoramento de serviços, com destaque para o resgate do domicílio como ambiente terapêutico e a reorganização da Atenção Domiciliar (AD) como estratégia de atenção no âmbito do Sistema Único de Saúde (SUS) (WACHS et al, 2016;BRAGA et al, 2017).…”
unclassified
“…Isso porque, além de ampliar a sua autonomia e de suas famílias -aspecto importante uma vez que, conforme colocado, em muitas delas encontram-se os cuidadores -evita, sobremaneira, hospitalizações desnecessárias de idosos, diminuindo, assim, não apenas riscos sociais, mas também aqueles relacionados à permanência em estruturas tradicionais hospitalares (Brasil, 2013;Feuerwerker, & Merhy, 2008;Lima, Spagnuolo, & Patrício, 2013 (Wachs, Nunes, Soares, Facchini, & Thumé, 2016). Esses dados indicam a crescente demanda por esse tipo de assistência num contexto de aumento da proporção de idosos e da prevalência de doenças crônicas.…”
Section: Introductionunclassified